Pengaruh External Pressure, Nature of Industry dan Rationalization Terhadap Financial Statement Fraud: Pengaruh External Pressure, Nature of Industry dan Rationalization Terhadap Financial Statement Fraud - Siti Salamah, Ayu; Marliani, Nenda (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2025)
This study endeavors to delineate and empirically examine the impact of external pressure, the nature of industry, and rationalization on financial statement fraud. The conflicting results observed in prior research provided the impetus for this re-examination within the specified context. The research sample comprised 42 entities classified under the Energy sector, specifically the Oil, Gas, and Coal sub-sector, listed on the Indonesia Stock Exchange between 2019 and 2023. A descriptive and verificative research methodology was adopted, with data analysis performed using multiple linear regression via EViews 9 software. The analytical outcomes revealed that: (1) external pressure exerted a negative and statistically significant effect on financial statement fraud; (2) the nature of industry demonstrated a negative and statistically insignificant effect on financial statement fraud, suggesting that a company's pursuit of an ideal state does not inherently preclude the occurrence of fraudulent activities; and (3) rationalization exhibited a negative and statistically insignificant effect on financial statement fraud.